Efecto del tiempo de temple y tiempo de revenido sobre la dureza, resistencia a la tensión y ductilidad en una aleación cuproaluminio cobre - 10% aluminio tesis - Chávez Amaya, Edgar Enrique (2016)
In this research studies the effect of Quenching time and tempering time on hardness, tensile strength and ductility of cuproaluminium alloy Cu - 10% Al, pouring sand mold. It used quenching time of 1, 2, and 3 hours at 900° C and tempering time of 1, 2, and 3 hours at 400° C. The hardness test was performed according to the ASTM E-140 standard and tensile test to the ASTM E-8 standard. The results obtained show that decrease the hardness and tensile strength, while increases ductility with the increase in the quenching time and tempering time. Higher values obtained test specimens of hardness and tensile strength were heated at 900 ° C for 1 hour with water quenching and tempering at 400 ° C for times of 1, 2 and 3 hours. And the best ductility values obtained for test specimens were heated at 900 ° C for 3 hours with water quenching and tempering at 400 ° C for times of 1, 2 and 3 hours. That, in the cuproaluminium alloy Cu - 10% Al, Quenching time 1 hour at 900 ° C and tempering time of 1 hour at 400 ° C is optimum, these conditions hardness values, tensile strength and adequate ductility were obtained. It is concluded that the Quenching time of 1 to 3 hours at 900 ° C and tempering time from 1 to 3 hours at 400 ° C significantly affects the properties evaluated on the cuproaluminium alloy Cu - 10%Al pouring sand mold, according to the statistical analysis with a confidence level of 95 %. Keyword: Quenching time, tempering time, cuproaluminium, hardness, tensile strength, ductility.